2020
DOI: 10.3389/fpsyt.2020.578682
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Paternal Involvement, Relationship Satisfaction, Mothers' Mental Health and Parenting Stress: A Multi-Sample Path Analysis

Abstract: Research has demonstrated the short-and long-term impacts of maternal mental health and well-being on children's emotional and behavioral outcomes. It is thus important to better understand the antecedents of maternal depression and stress. The aim of this study was to determine whether the contribution of perceived paternal involvement to account for mothers' depression and parental stress was mediated by relationship factors such as parenting alliance and dyadic adjustment. A second aim was to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Furthermore, this study reveals significant associations among parent-child relationships, marital relationships and parent mental health. Following existing studies, the results suggest that parents with higher quality marital and parent-child relationships report fewer mental health symptoms [ 32 , 46 ]. This finding is supported by the social support theory field [ 46 ], wherein the relationship perspective states that relationships enhance mental well-being by providing companionship and intimacy [ 47 ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, this study reveals significant associations among parent-child relationships, marital relationships and parent mental health. Following existing studies, the results suggest that parents with higher quality marital and parent-child relationships report fewer mental health symptoms [ 32 , 46 ]. This finding is supported by the social support theory field [ 46 ], wherein the relationship perspective states that relationships enhance mental well-being by providing companionship and intimacy [ 47 ].…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, previous research has shown that a positive family relationship benefits parent mental health. In contrast, an insecure attachment with children or partners can lead to mental health issues such as stress and depression symptoms [ 32 , 33 ]. Thus, it is reasonable for this study to assume that parents with better family relationships and more terrific family cohesion would report fewer mental health symptoms during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the associations between parental depression, child internalizing and externalizing problems, and parenting stress have been explored by extensive research, few studies have explored the roles of parenting stress in the relationships between parental depression and child internalizing and externalizing problems, particularly in children of preschool age. Parents with high levels of depression may have attention biases to negative information ( 29 ), which may increase parenting stress ( 30 ), and, finally, contribute to child internalizing and externalizing problems ( 31 ). Thus, we hypothesize that parenting stress mediates the relationships between parental depression and child internalizing and externalizing problems within the Chinese cultural context.…”
Section: Parental Depression Internalizing and Externalizing Problems...mentioning
confidence: 99%
“…While the studies have shown that there is a statistically significant negative relation between fathers' involvement and mothers stress in families having children with autism. (DeMontigny et al, 2020 ; Hu et al, 2017 ). However, the emerging disease of COVID‐19 can affect the care burden and coping styles methods of these parents.…”
Section: Introductionmentioning
confidence: 99%